Pengembangan Media E-Learning Koi Park Berbasis Scan QR Android pada Mata Pelajaran Kewirausahaan di SMK Negeri 1 Udanawu - Wahyudi, Erlik Prasetyo; Tuwoso, Tuwoso; Prasetya, Didik Dwi (Universitas Nahdlatul Ulama Blitar, 2025)
Currently, technology has changed the paradigm of how educators teach and how students learn in obtaining various sources of learning information. Entrepreneurship subjects in vocational schools require teachers to provide real-world implementation in presenting entrepreneurial literacy material, so that they can develop the potential of MSMEs around the school area. One of the potentials for MSMEs is Koi fish cultivation in Kemloko Village, Nglegok District, Blitar Regency. This research aims to develop the Koi Park Blitar e-learning media application based on Android QR Scan in Entrepreneurship subjects using the ADDIE model. The learning media is suitable for use with validation results by material experts of 96.15 (very feasible) and media experts of 92.30 (very feasible).